Therapeutic effect of erythropoietin and its derivatives in the treatment of acute ischemic stroke - Ramón Rama; Joan Ramon Torrella (Exploration of Neuroprotective Therapy)
Stroke is the third leading cause of death and disability in industrialized countries. The estimated costs of stroke to the healthcare system are $85 billion in the United States and $40 billion in the European Union. Despite the extensive research over the past decades, only therapies aimed at restoring blood flow to the affected area have been successful. However, the high risk of causing intracranial hemorrhage limits the application of this type of therapy to a small number of patients. Several studies have shown that, in addition to its well-known regulatory function in erythropoiesis, erythropoietin (EPO) is a potent neuroprotective agent against ischemic stroke. However, the use of EPO to treat stroke requires long-term protocols, high doses, and multiple administrations, which may cause thromboembolic complications due to increased hematocrit and blood viscosity, making EPO treatment unsuitable. To mitigate these adverse effects, various EPO analogues with neuroprotective properties but lacking erythropoietic activity have been investigated. This review aims to provide an overview of the protective mechanisms of EPO and its derivatives in the treatment of stroke.